Aplikasi Otentikasi Citra Digital Dengan Metode Adaptive Data Hiding - Zalukhu, Damarlin (MEANS (Media Informasi Analisa dan Sistem), 2018)
Problems that often occur in internet services make data security not guaranteed. To provide content authentication and duplicate protection from digital data, two complementary techniques have been developed, namely encryption and watermarks. Encryption techniques are used to secure digital data during transmission from sender to receiver. Because digital images can be easily reproduced, cryptosystems cannot solve this problem perfectly. The second security measure that completes encryption is to attach a secret signal, a watermark, directly to the original data so that it remains available during use. Watermarking cannot prevent duplication, modification and distribution of digital media by itself, so it must be combined with cryptography. Embedding is done by modifying the average pixel intensity value of each block in the range determined by the contrast value for a particular block. This reduces the effect of modification as felt by the human eye. The extraction procedure calculates and compares the number of pixel values for blocks of the original image and watermark. The results show the robustness of the scheme towards general image processing operations such as cropping, modification, low pass filters, median pass filters, minimized and lossy JPEG compression with various quality index factors. The results also illustrate that the watermark is safe, restored and recognized even after the watermark image has been damaged, forged and modified by a general image processing operation. A comparative study of the scheme proposed with the existing scheme has also been carried out to observe the strength of the scheme.